Polymer-metal complex based on copper(II) acetate and polyvinyl alcohol: thermodynamic and catalytic properties - Kuralay S. Maksotova; Dariya T. Kalikh; Arnur T. Omirzakova; Botagoz S. Bakirova; Dina N. Akbayeva (Chimica Techno Acta)
In this work we obtained a polymer-metal complex by mixing aqueous solution of copper(II) acetate with PVA at a certain ratio, pH of the solution and temperature. The composition of the complex compound was determined by potentiometric and conductometric titration. The possibility of a complex formation was proved by calculating thermodynamic characteristics. The stability constant of the polymer-metal complex was calculated on the basis of the modified Bjerrum’s method. The metal-polymer complex was synthesized in the ratio 1:2. IR spectroscopy and scanning electron microscopy (SEM) confirmed the coordination of polymeric PVA ligand to copper and allowed evaluating the morphology and features of the complex surface. The catalytic activity of the synthesized compound was evaluated in the oxidation reaction of elemental phosphorus (P4) by oxygen in aqueous-organic media under mild conditions. Quantitative analysis of phosphoric acid was made by photocolorimetric method. We found that the oxidation process of P4 in the presence of the complex Cu(PVA)2(OAc)2 in aqueous-organic media is characterized with the maximum absorption rate, in comparison with Cu(OAc)2·H2O oxidation process with P4, and yields up to 97% of the products. The process of oxidation of yellow phosphorus by oxygen in the presence of the copper(II)-PVA complex proceeds through key reactions of two-electron reduction of the catalyst P4 with the formation of intermediate phosphorus-containing products P3+ and the stages of catalyst regeneration by oxygen. Twenty-electron oxidation of P4 to the phosphorus-containing P5+ products involves 10 two-electron redox reactions and a number of complexation or hydrolysis stages.